MICROBIOLOGICAL AND PHYSICOCHEMICAL QUALITY OF HOSPITAL “X” EFFLUENT IN ABA, ABIA STATE, NIGERIA. - C. C, Ike,; D. K., Akwari, (IJRDO-Journal of Applied Science, 2017)
The microbiological and physicochemical quality of hospital “x” effluent was assessed. The study was done using standard microbiological and physicochemical methods. Bioloads had highest counts in the late hour (LH) samples than in the early hour (EH) samples: total heterotrophic bacteria (CFU/ml) - 7.9 x 104 ± 0.15 (LH), 6.7 x 104± 0.20 (EH), total coliform (CFU/ml) - 2.2 x 10³ ± 0.09 (LH), 1.8 x 10³ ± 0.04 (EH), and fungi (CFU/ml) - 3.5 x 10³ ± 0.05 (LH), 3.1 x 10³ ± 0.17 (EH), The recorded bioload results were higher than regulatory standards as stipulated by National Environmental Standards and Regulatory Enforcement Agency (NESREA). Most of the physicochemical values were high in the LH samples than in EH samples, and all the values are above regulatory standards (NESREA) except for temperature and nitrate that had values below standards. Total phosphorus had values slightly above regulatory standards (NESREA). A total of four bacterial species (Escherichia coli, Salmonella, Staphylococcus and Enterobacter species) and four fungal species (Aspergillus, Candida, Cryptococcus and Penicillium species) were isolated respectively. Escherichia coli had the highest prevalence for bacteria (33.3%), while Aspergillus species had the highest prevalence for fungi (42.9%). This study has shown that hospital wastewater/ effluent is highly polluted, contaminated, infectious and if discharged into the environment untreated, it can pose serious health hazards to humans. Therefore, there is need for strict regulations concerning treatments and monitoring by regulatory bodies on the affected establishments to avert epidemics.